Patristic Divergences about the Image of God in Man - Hall, Stuart George (Studies in church history, 2007)
The pathologically pious heresy-hunter Epiphanius, bishop of Salamis from 365 to 403, might be reckoned a champion of uniformity in the Church. Notoriously he promoted the campaign against Origen in Palestine, and in his Panarion attacks Origen’s theology at length. Never the brightest of the Fathers, he was confused by the question of the image of God in man. He comes to it when considering the sect of Audians, who were anthropomorphites; that is, they held God to have a bodily form which the human body replicates. According to Genesis 1: 26-7, God made man, male and female, in (after, according to) the image and likeness of God When Epiphanius gets to the detail of the Audian argument, it is plain that they argued from the use in Scripture of bodily language about God’s eyes, hand, feet, and other organs, and from the Lord’s appearances to Moses and the prophets, to demonstrate his bodily shape. Epiphanius can refute this in detail, but is aware of other suggestions about wherein what is ‘in the image’ consists, and regards none as wholly coherent with orthodox faith and Scripture. He mentions the theories that it is the soul that is in the image, or that it is virtue, or that it is the grace received in baptism, or that it applied to Adam only before his sin.